2009
DOI: 10.1071/fp09150
|View full text |Cite
|
Sign up to set email alerts
|

Root phenomics of crops: opportunities and challenges

Abstract: Reliable techniques for screening large numbers of plants for root traits are still being developed, but include aeroponic, hydroponic and agar plate systems. Coupled with digital cameras and image analysis software, these systems permit the rapid measurement of root numbers, length and diameter in moderate (typically <1000) numbers of plants. Usually such systems are employed with relatively small seedlings, and information is recorded in 2D. Recent developments in X-ray microtomography have facilitated 3D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
113
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 168 publications
(114 citation statements)
references
References 39 publications
1
113
0
Order By: Relevance
“…For example, Wojciechowski et al (2009) showed that the effect of Rht genes on root growth was strongly positive in gel cultures but strongly negative in soil. Potential approaches for efficient phenotyping of root traits under controlled conditions have recently been reviewed by Gregory et al (2009), who indicated significant emerging capability. However, field screening remains difficult.…”
Section: Lessons From Individual Root Traits For Water Capturementioning
confidence: 99%
“…For example, Wojciechowski et al (2009) showed that the effect of Rht genes on root growth was strongly positive in gel cultures but strongly negative in soil. Potential approaches for efficient phenotyping of root traits under controlled conditions have recently been reviewed by Gregory et al (2009), who indicated significant emerging capability. However, field screening remains difficult.…”
Section: Lessons From Individual Root Traits For Water Capturementioning
confidence: 99%
“…These include growth on moistened germination paper rolls or pouches, sand rhizotrons, rhizoboxes, in compost followed by washing, soil columns and gelbased systems where phenotypic effects can be imaged using flatbed scanners, digital cameras, lasers, or even x-ray computed tomography (CT) (Hetz et al, 1996;Whiting et al, 2000;Bengough et al, 2004;Fang et al, 2009;French et al, 2009;Gregory et al, 2009;Hammond et al, 2009;Iyer-Pascuzzi et al, 2010;Trachsel et al, 2010;Tracy et al, 2010Tracy et al, , 2011Chapman et al, 2011;Lobet et al, 2011;Lucas et al, 2011). Magnetic resonance imaging (for noninvasive analysis of root structures) and positron emission tomography (for analysis of carbon transport and accumulation) can be combined to study the dynamics of structure-function relationships of roots in real soils in a noninvasive manner .…”
Section: How To Image Root Systems?mentioning
confidence: 99%
“…Root architecture directly impacts the capture of such soil resources and is, therefore, fundamental to crop productivity (Lynch 1995;Casson and Lindsey 2003;Malamy 2005;Watt et al 2006;Dunbabin 2007;Fita et al 2008;Gregory et al 2009). Changes in root system architecture and exploitation of soil water influence the accumulation of crop biomass (Hammer et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Quantifying the architecture of root systems is essential because crop productivity is almost always influenced by the availability and accessibility of water and nutrients that are heterogeneously distributed in the soil (Miller et al 2003;Cichy et al 2009;Gregory et al 2009). Root architecture directly impacts the capture of such soil resources and is, therefore, fundamental to crop productivity (Lynch 1995;Casson and Lindsey 2003;Malamy 2005;Watt et al 2006;Dunbabin 2007;Fita et al 2008;Gregory et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation